Performance measurement using overall equipment and resource effectiveness - A concrete block manufacturing case study - Huthaifa Alkhazraji; Sohaib Khlil; Zina Alabacy (Journal of Techniques)
Companies are required to integrate a set of critical dimensions in order to measure and evaluate their performance to compete in globally competitive markets. Overall Equipment Effectiveness (OEE) is a quantitative metric, in the context of the total productive maintenance (TPM), attempts to measure and improve the effectiveness of manufacturing operations in three dimensions namely: availability, performance rate and quality rate. This study applies OEE to evaluate and improve the performance of a concrete block manufacturing system at Dler Company in Iraq. The study was conducted in two years of operation during 2016 and 2017. Results from 2016 show that the level of effectiveness was lower than the world class. An improvement in the average value of the OEE for 2017 was recorded, where the OEE value is increased in 2017 to 75% in comparison with its value in 2016 at 67%. It was also found that the reasons for this improvement are due to the enhancement that are made in the availability and quality.